Propuesta de mejora de los Procesos de Definición del Alacance y Estimación del Tiempo en Proyectos de Análisis de Integridad Estructural - Correal-Gómez, Luis (Instituto Tecnológico de Costa Rica, 2013)
The reader of this document will find a process improvement proposal to strengthen the scope definition process, initial time estimates, risk identification and response, and changes control for structural analysis projects developed at Technomeca S.A. The main problem currently faced by this company resides on the difficulties and inconsistencies between the initial baselines and the project end result. Overall intention is to be able to transition from just a technical perspective and technical driven working culture to a technical/administrated working culture since Technomeca faces a complete lack of formal processes of project management. This company has recognized the importance and potential benefits of incorporating Project Management best practices to its working culture and has decided to start this initiative by strengthening its immediate need areas. Although this company provides different engineering services, the improvement proposal is oriented specifically towards structural analysis projects since these comprehend the majority of the company’s workload and also gives Technomeca a competitive edge due to the complexity and lack of this type of engineering service in Costa Rica. This approach will serve as a first step to gradually introduce the company into Project Management activities while addressing their primary need.
Proyecto de Graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2012.
Keywords: Administración; Procesos; Propuesta; Estudio de tiempos; Mejoramiento continuo